Defect formation and bending properties in graphite under He atom implantation investigated by molecular dynamics method. (May 2022) - Long, X.H.; Setyawan, W.; Tai, K.P.; Liu, Y.; Yu, M.S.; Wang, Z.Q.; Gao, N.; Wang, X.L.
Abstract: The formation and evolution of radiation defects and their effects on bending property of a single graphite under low energy helium atom implantation have been studied at atomic scale through molecular dynamics simulations. Various simple interstitial and vacancy defects are observed during the implantation process, which is a function of incident energy and cross section of helium-carbon interaction. Large defects are observed after continuous helium atom implantations. The effects of incident energy on the density, size and distribution of defects are analyzed in detail. Furthermore, the kinetic evolution process of radiation defects at different annealing temperatures have also been simulated, including the migration, aggregation, transformation, coalescence, and self-healing. The large defect clusters, crossing several carbon layers, have been confirmed to be the primary reasons that affect the bending property of graphite. All these results provide a new understanding for further applications of graphite in nuclear reactors. Graphical abstract: Image 1